Intangible Assets and Intellectual Capital as Key Factors of Romania's Convergence - Marta Cristina Suciu (Romanian Academy, National Institute for Economic Research, 2009)
The main aim of the chapter is to provide the readers with a synthesis of the new international framework of debate dedicated to the topics of intangible assets and intellectual capital. Considering the topics of the whole book, this chapter is focussed on the role played by intangible assets and intellectual capital for attaining convergence and for increasing competitiveness. * Study within the CEEX Programme Project No. 220/2006 Economic Convergence and Role of Knowledge in Relation to the EU Integration .
Keywords: E24; I23; I28; J24; O15; O47; 330; convergence; knowledge-based economy; competitiveness; competitive advantage; intangible assets; intellectual capital